Adsorption of Cr(Vi) Ion from Aqueous Solutions by Solid Waste of Potato Peels - Mohammed, Nidhal M.Sh.; Mohammad Salim, Haydar A. (Science Journal of University of Zakho, 2017)
Pollution of wastewater with heavy metal has always been a serious problem to the environment. Chromium is considered one of the most noxious heavy metals. Adsorption is now reorganized as an alternative technology of defence for chromium removal due to local availability, technical efficiency and cost effectiveness. Potato peel powder can be used as a low cost biosorbent to remove hexavalent chromium from aqueous solutions under various experimental conditions. Different parameters including equilibrium contact time, initial metal ion concentration, potato peel dose, pH and temperature were studied through a number of batch sorption experiments. Both the Langmuir and Freundlich were found to fit the adsorption isotherm of Cr (VI) ion onto potato peel. The Langmuir adsorption capacity was found to be 1.97 mg/g while Freundlich constants including Kf and n were 1.57 and 2.5, respectively. The adsorption kinetic was found to be more fit with the pseudo-first order model. This study showed a high efficiency of potato peel for the biosorption of Cr (VI) ion from aqueous solutions.